Attention-Based User Interface Design for a Tele-Operated Crane - Chen, Y.; Chi, Hung-Lin; Kang, S.; Hsieh, S. (American Society of Civil Engineering, 2016)
During crane operation, the operator can be distracted by a multitude of factors, leading to hazardous operational environments which can result in accidents. Recent investigations into the potentials of tele-operation have revealed that risks to human safety at the jobsite can be reduced drastically with the removal of the need for many personnel to be physically onsite. This research focused on the interface design of a tele-operated crane considering human attention by using markerless augmented reality (AR) technologies. The attention-based interface has been designed with consideration of how the users' attention is divided into three view types: focused views, ambient views, and alert views. To verify the usability of the interface, a user test is conducted in a simulated environment using a robot arm. The results indicate that the interface prevented 57% of collisions possibility. The authors also found that the interface resulted in high levels of user satisfaction. The utility rate of the different view types was found to be correlated with general erection activities. The research results provide an ideal reference for designing user interfaces of tele-operated cranes in the future.